6(x-6)+6=8x-12X=

Simple and best practice solution for 6(x-6)+6=8x-12X= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-6)+6=8x-12X= equation:



6(x-6)+6=8x-12x=
We move all terms to the left:
6(x-6)+6-(8x-12x)=0
We add all the numbers together, and all the variables
6(x-6)-(-4x)+6=0
We multiply parentheses
6x-(-4x)-36+6=0
We get rid of parentheses
6x+4x-36+6=0
We add all the numbers together, and all the variables
10x-30=0
We move all terms containing x to the left, all other terms to the right
10x=30
x=30/10
x=3

See similar equations:

| 9X+X-5X=5x6 | | 7=x-8/3+8 | | 22h+16=8h+72 | | -2(7g)=30 | | y+7(-2)=10 | | t-4.25=-4 | | 3x-30=15-2x | | 4x-6+4x-2=32 | | x(2)=9/100 | | (5x+6)-2(x-1)=3 | | 5x-3/2=x-5 | | x/1.5=16 | | 5x4-10x3-2x2=0 | | F(x)=-3x+15 | | 5x+9=5x+1 | | 5x4−10x3−2x2=05x4-10x3-2x2=0 | | 4-4(x+1)=4x-32 | | x2=5x | | x2-5x=7.5 | | 3=x-8/3 | | x+4/x+1=3 | | -8=x/2-9 | | h+3.13/2=3*3.14/2 | | 1y-3(2y-7)=76 | | 3.50r+2r+7-2=5 | | 5-2x=-1-3x | | -4(-2x+3)=-52 | | -4x+12=-4-4x+12=-4 | | 3m2+m=30 | | 2r+19=20 | | 4x-(-x-5)=20 | | 45+5/6x=60 |

Equations solver categories